Knowledge Hiding: One of the Primary Reasons behind the Rapid Spread of the Novel Coronavirus COVID-19 - Issac Abraham Cyril (Sciendo, 2021)
The world is battling out the pandemic of Covid-19. The World Health Organization (WHO) is jointly acting upon the same daily, which is evident from the ‘situation reports.’ The pandemic, which saw its origin in Wuhan, has spread across the world within a short span of under two months. While the pandemic has effectively instilled a situation of cordon sanitaire across the globe, the virus seems to show no respite. This study collates different sources and establishes the human tendency of knowledge hiding as the prime reason for the spread of such colossal magnitudes. The study underlines the notion by examining some of the critical cases and situations that have unfolded in the very recent past.